Circadian dependency of microglial heme oxygenase-1 expression and inflammation determine neuronal injury in hemorrhagic stroke - Luise Henrich; Iva Kiessling; Matti Steimer; Sibylle Frase; Sandra Kaiser; Nils Schallner (BMC, 2023)
Abstract Background The heme oxygenase-1 (HO-1) enzyme pathway is of crucial importance in the removal of toxic blood components and regulation of neuroinflammation following hemorrhagic stroke. Although a circadian pattern dependency in the incidence and severity of hemorrhagic stroke exists, it is unknown whether the activity of the HO-1 system in the context of hemorrhagic injury also exhibits circadian dependency. We hypothesized that the circadian regulation of microglial HO-1 would determine the extent of neuroinflammation and neuronal injury in a murine model of subarachnoid hemorrhage (SAH). Methods In vitro expression patterns of HO-1 and circadian rhythm genes were analyzed in the microglial BV-2 cell line and primary microglia (PMG) using Western blot and qPCR. PMG isolated from Hmox1 fl/fl and LyzM-Cre-Hmox1 fl/fl mice were used to evaluate the role of microglial HO-1. We further investigated the in vivo relevance in a murine subarachnoid hemorrhage (SAH) model using Hmox1 fl/fl and LyzM-Cre-Hmox1 fl/fl mice with myeloid cell HO-1 deficiency, inducing SAH at different zeitgeber (ZT) times and analyzing the expression of HO-1 and the circadian control gene Period-2 (Per-2), respectively. Furthermore, we measured the inflammatory cytokine Monocyte Chemoattractant Protein-1 (MCP-1) in the cerebrospinal fluid of SAH patients in correlation with clinical outcome. Results HO-1 baseline expression and response to CO with blood exposure depended on ZT. In vitro expression of circadian control genes was de-synchronized in LyzM-Cre-Hmox1 fl/fl PMG and did not respond to exogenous CO exposure. We found that circadian rhythm plays a crucial role in brain damage after SAH. At ZT2, we observed less phagocytic function, more vasospasm and increased microglial activation. CO reduced mortality at ZT12 in HO-1 deficient mice and reduced the difference between ZT2 and ZT12 in the inflammatory response. Induction of MCP-1 in the CSF from SAH patients was time-dependent and correlated with the expression of circadian control genes, SAH severity, functional impairment and delirium. Conclusions Our data point towards a crucial role for the HO-1 enzyme system and circadian control in neuronal injury after a hemorrhagic stroke.